Der Zusammenhang von ADHS, Verhaltensproblemen und Schulerfolg am Beispiel der Grundschulempfehlung - Jantzer, Vanessa; Haffner, Johann; Parzer, Peter; Resch, Franz (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2012)
The Relationship Between ADHD, Problem Behaviour and Academic Achievement at the End of Primary School So far there are contradictory findings concerning the degree of negative influence of attention deficit disorders, external or socio-emotional disorders on academic development of a child. Therefore the present epidemiologic study analyses the relationship between clinically relevant problems and academic achievement of fourth graders (measured by recommendation for secondary school: A-level, B-level or C-level). Children (N = 3910) were rated by their parents by anonymised questionnaires (Child Behavior Checklist CBCL) at the end of primary school. Especially in the field of attention deficit, somatic and anxiety/ depression disorders, many children were in a clinically relevant range compared to German norm data. It became obvious that future C-level pupils are particularly strong, multiply problem troubled, with constantly higher problems at all subscales. Mainly attention deficit disorders proved to be relevant for academic achievement, but also delinquent behaviour and social problems, which enhance the relative risk of recommendation for B- or C-level considerably. Early applied preventive interventions supporting social and cognitive development seem therefore of central importance for the school career of primary school children.